(NfORTEPIANNYE PROIZWEDENIIQ l(B. (NqNA^EKAs (NmONOGRAFIQs - (Nl(B. (Nw(B.. (NmAJLINGOWAs ((NmOSKWAs (NMUZYKAs, 1986)
(NkNIGU FORTEPIANNYE PROIZWEDENIQ l(B. (NqNA^EKA S INTERESOM VDUT NE TOLXKO PIANISTY NO WSE KOMU DOROG qNE^EK(B.s
Keywords: (NmONOGRAFIQs